Development and preliminary validation of the Child & Adolescent Social Cognitions Questionnaire - Leigh, E; Clark, DM (Springer, 2021)
Negative cognitions play a central role in adolescent social anxiety, and yet there is a lack of empirically validated measures assessing these in detail. This study describes the adaptation of the Child & Adolescent Social Cognitions Questionnaire (CASCQ) from the adult version of the scale and its preliminary validation in a general adolescent school sample (N = 671). Exploratory and confirmatory factor analysis on split halves of the data indicated two factors, labelled ‘negative self-concept’ and ‘anxious appearance’, provided the best fit. Totals and subscales possessed good internal consistency and convergent validity. Findings suggest that the CASCQ is a reliable and valid measure of social anxiety-related cognitions in youth and may be useful for research and clinical purposes. Further examination of the scale with pre-adolescents and clinical samples is warranted.